The Effects of Nitric Oxide Donors on Uterine Artery and Sub-endometrial Blood Flow in Patients with Unexplained Recurrent Abortion - M Abdel-Razik; S El-Berry; A Mostafa (JRI, 2014)
Background: Nitric oxide plays a major role in increasing uterine blood flow during the luteal phase and early pregnancy. This study was done to compare uterine artery and sub-endometrial blood flow indices during the luteal phase between patients with unexplained recurrent abortion and fertile women and also to evaluate the effects of nitric oxide donors on blood flow indices in the abortion group. Methods: The study included a control group of 30 primiparae who had normal vaginal delivery and no history of abortion and an abortion group of 30 nulliparous women with history of two or more unexplained recurrent abortions. Transvaginal three-dimensional pulsed color Doppler ultrasound was done on days 21-23 of the cycle to measure uterine artery resistance and pulsation indices and the subendometrial vascular, flow and vascular-flow indices. Isosorbide mononitrate 20 mg tablet was administered vaginally in the abortion group and blood flow indices were measured again after two hours. The Student t-test and the paired t-test were used for analysis of results and a p-value of ≤0.05 was considered significant. Results: Patients with unexplained recurrent abortion had significantly higher uterine artery resistance and pulsation indices and lower sub-endometrial vascular, flow and vascular-flow index (p<0.01-0.0001). Isosorbide mononitrite significantly decreased uterine artery and increased sub-endometrial blood flow indices (p<0.001). Conclusion: Uterine artery and sub-endometrial blood flow decreased during the luteal phase in patients with unexplained recurrent abortion. Nitric oxide donors increased blood flow and may be of a therapeutic value.